2009
DOI: 10.2215/cjn.04950908
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Therapy, Hemoglobin Targets, and Quality of Life in Healthy Hemodialysis Patients

Abstract: Background and objectives: The effects of different hemoglobin targets when using erythropoiesis-stimulating agents on quality of life are somewhat controversial, and predictors of change in quality of life in endstage renal disease have not been well characterized.Design, setting, participants, & measurements: Five hundred ninety-six incident hemodialysis patients without symptomatic cardiac disease were randomly assigned to hemoglobin targets of 9.5 to 11.5 g/dl or 13.5 to 14.5 g/dl for 96 weeks, using epoet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
62
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 17 publications
0
62
0
1
Order By: Relevance
“…Study size (N) is indicated by the bars on the left (15). changes with rHuEPOs (for a more detailed account see references [17,18]). By the early part of this new millennium, at a stage that in retrospect will be seen to be a "high Hb mark" for rHuEPOs, there were calls from guidelines groups (19) for more complete correction (which becomes, with each 1 g/dl of attempted correction, noticeably more expensive and more difficult to achieve).…”
Section: What Has Gone Wrong?mentioning
confidence: 99%
“…Study size (N) is indicated by the bars on the left (15). changes with rHuEPOs (for a more detailed account see references [17,18]). By the early part of this new millennium, at a stage that in retrospect will be seen to be a "high Hb mark" for rHuEPOs, there were calls from guidelines groups (19) for more complete correction (which becomes, with each 1 g/dl of attempted correction, noticeably more expensive and more difficult to achieve).…”
Section: What Has Gone Wrong?mentioning
confidence: 99%
“…The use of ESA has beneficial effects by correcting anemia and their associated symptoms and improving patients' quality of life [50,51]. However, the effects of ESA on the progression of renal function are controversial.…”
Section: Erythropoiesis-stimulating Agents In Ckd-anemiamentioning
confidence: 99%
“…Some studies have suggested the possible relationship between the variability of the hemoglobin level and the patient [138,139] . Although there is variability in the results of different studies [120,131,[140][141][142][143] , the most consistent observation is that there are better results in terms of quality of life, with no increase in adverse reactions of hemoglobin in the range of 11-12 g/dL (hematocrit 33%) compared with lower levels [139][140][141][142][143][144] . There is a large study under way in relation to the normalization of hemoglobin.…”
Section: Hemoglobin Targetmentioning
confidence: 99%
“…Data from recent studies in CKD patients indicate increased morbidity and mortality in relation to high levels of hemoglobin (normal) [130][131][132][133] , as in patients with cancer [103,104] . It seems appropriate to establish a target hemoglobin level of 11-12 g/dL, which demonstrates greater benefit in quality of life and costeffectiveness in renal patients [120,133,[139][140][141][142][143][144][145] .…”
Section: Hemoglobin Targetmentioning
confidence: 99%